2019
DOI: 10.1515/nanoph-2019-0056
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of highly homogeneous and controllable nanogratings on silicon via chemical etching-assisted femtosecond laser modification

Abstract: Femtosecond laser direct writing is widely exploited in surface periodic structures processing. However, this technique still faces challenges in obtaining high surface homogeneity and flexible morphology controllability. In this study, a flexible and efficient approach has been proposed to fabricate highly homogeneous and controllable nanogratings on silicon via chemical etching-assisted femtosecond laser modification. By precisely manipulating the laser-material interaction process, alternating amorphous-cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 50 publications
1
35
1
Order By: Relevance
“…The film thickness is decreased by~40 nm as a whole, and the depth between the ridges and valleys is~65 nm scanning speed, the time consumption here can be decreased by at least 4 orders of magnitude when texturing a surface area of 10 × 12 mm 2 . In addition, different from the observations of a low-spatial-frequency LIPSS reported on other materials [23][24][25][26][27] , the spatial orientation of our achieved structures is shown to be strictly parallel to the direction of the linear polarization of the incident laser ( Fig. 1d).…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…The film thickness is decreased by~40 nm as a whole, and the depth between the ridges and valleys is~65 nm scanning speed, the time consumption here can be decreased by at least 4 orders of magnitude when texturing a surface area of 10 × 12 mm 2 . In addition, different from the observations of a low-spatial-frequency LIPSS reported on other materials [23][24][25][26][27] , the spatial orientation of our achieved structures is shown to be strictly parallel to the direction of the linear polarization of the incident laser ( Fig. 1d).…”
Section: Resultscontrasting
confidence: 99%
“…The FPL strategy has also been proven to be capable of breaking the diffraction limit by applying suitable experimental parameters 21,47 . Apart from this, we should also emphasize that the phenomenon here is different from others, although similar works have been covered in previous reports [23][24][25][26][27] . The spatial orientation of the grating is parallel rather than perpendicular to the polarization direction of the incident light, leading to a completely different analysis of the laser-matter interaction.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Of interest, one-dimensional (1D) femtosecond laser-induced periodic surface structures (fs-LIPSSs) with subwavelength periodicity that can be realised on a wide range of materials have attracted considerable attention 1,2 . Different techniques have been employed to address the spatial uniformity of fs-LIPSSs, for instance, positive and negative feedback mechanisms on titanium substrates 9 , chemicalassisted fs-laser-treatment 10 , high-uniformity fs-LIPSSs creation via temporally delayed multi-pulse irradiation 11,12 , non-ablative fs-laser structuring technique 13 , or self-organisation from metal-assisted pattern formation on glass 14 . While these studies showed the ability to produce more regular surface features, they did not demonstrate the ability to design the surface properties, which is crucial at the device engineering and application level.…”
Section: Introductionmentioning
confidence: 99%